2017
DOI: 10.1093/nar/gkx802
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 expression in thyroid and breast cancer requires the cooperation of three non-redundant enhancers under the control of BRD4 and c-JUN

Abstract: Aberrant reactivation of embryonic pathways is a common feature of cancer. RUNX2 is a transcription factor crucial during embryogenesis that is aberrantly reactivated in many tumors, including thyroid and breast cancer, where it promotes aggressiveness and metastatic spreading. Currently, the mechanisms driving RUNX2 expression in cancer are still largely unknown. Here we showed that RUNX2 transcription in thyroid and breast cancer requires the cooperation of three distantly located enhancers (ENHs) brought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 68 publications
(76 reference statements)
3
64
0
Order By: Relevance
“…As an oncogene, RUNX2 is frequently upregulated during the development of human cancer (20,21). Consistent with previous studies, the present study also illustrated significantly upregulated expression of RUNX2 in tumor tissues compared with that in adjacent healthy tissues in patients with TNBC.…”
Section: Discussionsupporting
confidence: 92%
“…As an oncogene, RUNX2 is frequently upregulated during the development of human cancer (20,21). Consistent with previous studies, the present study also illustrated significantly upregulated expression of RUNX2 in tumor tissues compared with that in adjacent healthy tissues in patients with TNBC.…”
Section: Discussionsupporting
confidence: 92%
“…RUNX2 is a member of the human RUNT related transcription factor family essential during embryogenesis for skeletal development. It was recognized on account of its oncogenic properties and many studies showed that a de‐regulating of RUNX2 function leads to progression and invasion of different tumours . Also, RUNX2 was reported to closely relate to bone formation and hypertrophic chondrocyte differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized on account of its oncogenic properties and many studies showed that a de-regulating of RUNX2 function leads to progression and invasion of different tumours. 12 Also, RUNX2 was reported to closely relate to bone formation and hypertrophic chondrocyte differentiation. 13 Some evidence showed that the down-regulated RUNX2 protein expression inhibited bone formation, and decreased bone mass.…”
mentioning
confidence: 99%
“…The motif-enrichment analysis implicated that RUNX2 was highly enriched in the opened regions of the controlled cells compared with JQ1-treating cells. RUNX2 was initially regarded as a promoter of osteoblast differentiation and was later proved to regulate the development of various tumors [31][32][33] . Guo et al 34 indicated that RUNX2 was highly expressed in human GC tissues and promoted the metastasis of GC by transcriptionally upregulating CXCR4 signaling, verifying the correlation between RUNX2 and GC progression.…”
Section: Discussionmentioning
confidence: 99%